TRENDS IN THE CATCH OF SILVERBELLIES BY MECHANISED BOATS IN TAMIL NADU DURING 1971-75 - Annam, V P; Dharmaraja, S K (Indian Journal of Fisheries, 2011)
Silverbellies form an important demersal fishery of India particularly onthe coasts of southern maritime states, the annual average catch amounting toabout 3% of the total marine fish CEtoh ia India. In Tamil Nadai, mechanised boatspredominantly operate at iRoyapuram (Kasimedai), Cuddflore, Portonovo, Adirampatnarri,Mandapam, Rameswaram and land considerable quantities of silverbellies.The catch trends of silverbellies landed by the mechanised boats in Tamil Naduduring the period 1971 to 1975 and the relation between the index of abundanceand the toU'l fishing effort both in respect of total landings and landings of silverbelliesare dealt with in the present paper.